A guide for the administration of oral antineoplastic in patients with swallowing disorders - Eduardo Tejedor-Tejada; Pablo Nieto-Guindo; Javier Tejedor-Tejada; Estrella Martínez-Velasco; Araceli Gómez-Sánchez (Farmacia Hospitalaria, 2021)
Objective: To review the available literature on the administration of oral antineoplastic drugs in patients with swallowing disorders and ystematize the information obtained. Method: Between September 2019 and April 2020, two hospital harmacists drew up a list of the oral antineoplastic drugs available in Spain, which was then distributed to three hospital pharmacists, each of whom carried out a literature search and a review. An analysis was made of the prescribing information and searches were performed in Pubmed, Micromedex, Uptodate, the Cancer Care Ontario website, different pharmaceutical bulletins, feeding tube administration guidelines, and tertiary information sources. Lastly, the pharmaceutical industry was contacted. The group systematized the information obtained, after which a fourth hospital pharmacist and an independent physician reviewed the work carried out. Results: A total of 64 oral antineoplastic drugs were reviewed. Relevant information was obtained for 48 drugs, of which 44 were amenable to administration to these patients (69% of the investigated drugs). A systematization of the information found was carried out. Conclusions: Despite having found different methods for preparing and administering most of the oral antineoplastic drugs reviewed, the information compiled was rather scarce and with a low level of evidence. Further studies, based on pharmacokinetic and stability studies, are necessary in this field as there is a sore need for oral liquid pharmaceutical forms or extemporaneous preparations allowing administration of oral antineoplastic drugs to these patients.